Caracterização fotométrica de aglomerados estelares nas regiões W 31 e NGC 6334 - Bianchin, Marina (2018)
Stellar clusters are groups of gravitationally bounded stars which were born from the same molecular cloud. In their initial phase, they remain bounded to the cloud and are called embedded clusters. These objects have ages of about 3Myr and the greater part of their stars are in the Pre Main Sequence (PMS). In the present work, we present a study of four embedded clusters, three of them in the region W31 and one in NGC6334. W31 is classified as a giant starforming region, presenting four HII regions and three stellar clusters, W31-CL, BDS 112 and one associated with G10:6-0:4, of which we will study the first two and the cluster towards SGR 1806-20. NGC6334, the Cat’s Paw Nebula, is known as a mini Starburst in the Galaxy, has at least five HII regions and several stellar clusters. There is evidence of the presence of a dust bridge that connects it with its twin region NGC6357. This bridge hosts the cluster VVVCL 109, studied here. The light absorption by the molecular cloud’s dust prevents the observation of embedded clusters in the optical wavelenghts. Therefore, we use the J, H and KS bands infrared photometry from the surveys VISTA Variables in the Vía Láctea survey (VVV) e The Two Micron All Sky Survey (2MASS). Both photometric data are combined in a way that the data for PMS and MS stars are available. The clusters’ structure is analysed through radial density profiles (RDPs) that, if the object is dinamically evolved, can be fitted by the King profile. We preform field star decontamination procedure in which the stars projected towards the cluster are taken off. The age, distance and extinction are calculated through the PARSEC isochrone fitting in the decontaminated CMD. The extinction is better examined through the color-color diagram. The clusters W31-CL and BDS 112 have ages ranging from 0 to 2 Myr and are located at a distance d = 4:7 kpc. We determined that the cluster SGR 1806-20 is associated to the regionW31, as it is located at the same distance as the other two. Besides that it has a maximum age of 4 Myr and extinction AV = 25 mag, caused by the dust accumulation in that direction. According to our analysis VVVCL 109 has about 1 Myr and a distance of d = 1:75 kpc, that localizes it in the molecular filament between NGC6334 and NGC6357.